(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
This research was conducted with the aim of analyzing and providing an overview of environmental pollution occurring around the Cipayung Final Disposal Site in Depok and its impact on the quality of life of the surrounding community. The type of research used is a descriptive qualitative approach with field observation methods. Data collection techniques were conducted through direct observation, informal interviews, and field documentation. The results of the study indicate that the environmental pollution found at the Cipayung Final Disposal Site in Depok includes air, water, and soil pollution. The pungent smell emanating from the decomposition of organic waste and methane gas emissions, the leachate produced is not fully processed and is at risk of contaminating groundwater and residents’ wells as water pollution, as well as piles of waste mixed with heavy metals and other hazardous substances, thus reducing soil quality as environmental pollution that is found. The health and economic impacts on the surrounding residents are also very significant due to the existence of the Cipayung Final Disposal Site. Penelitian ini dilakukan dengan tujuan untuk menganalisis dan memberikan gambaran mengenai pencemaran lingkungan yang terjadi di sekitar TPA Cipayung, Depok serta dampaknya terhadap kualitas hidup masyarakat sekitar. Jenis penelitian yang digunakan yaitu menggunakan pendekatan kualitatif deskriptif dengan metode observasi lapangan. Teknik pengumpulan data dilakukan dengan pengamatan langsung, wawancara informal, dan dokumentasi lapangan. Hasil dari penelitian menunjukkan bahwa pencemaran lingkungan yang ditemukan di TPA Cipayung, Depok meliputi pencemaran udara, air, dan tanah. Terciumnya bau menyengat yang berasal dari pembusukan sampah organik dan emisi gas metana, air lindi yang dihasilkan belum sepenuhnya terolah berisiko mencemari air tanah dan sumur warga sekitar sebagai pencemaran air, serta tumpukan sampah bercampur logam berat dan zat berbahaya lainnya sehingga menurunkan kualitas tanah sebagai pencemaran lingkungan yang ditemukan. Dampak kesehatan dan ekonomi warga sekitar juga sangat signifikan dari adanya Tempat Pemrosesan Akhir (TPA) Cipayung ini.